Analisis Kemampuan Literasi Sains (KLS) Peserta Didik Berdasarkan Asesmen PISA pada Mata Pelajaran IPA - Suaib, Andi; Mustami, Muh. Khalifah; Faisal, Faisal (Jurnal Biotek, 2025)
Science literacy is an essential aspect in assessing the extent to which students can understand, apply, and evaluate science concepts in everyday life, so analyzing this ability is necessary to determine the level of readiness of students in facing the challenges of the 21st century. The purpose of this study is to determine the science literacy skills of learners, identify factors that affect the science literacy skills of learners, and recommend strategies to improve the science literacy skills. The research method used was descriptive quantitative. The study population included all ninth-grade students of SMPN 52 Makassar, totaling 244 students. The research sample comprised 68 people, who were selected using purposive sampling. Data were collected through tests and questionnaires. The data analysis technique used was descriptive analysis. The results showed that students' science literacy skills were classified as “Very Low”, while the attitude aspects of students were classified as “High”. Factors influencing students' science literacy skills are also classified as “High”. The recommended strategy to improve science literacy skills is to use a variety of learning models or media so that students do not feel bored.